Insertion of four different types of supraglottic airway devices by emergency nurses. A mannequin-based simulation study. : Insertion of SADs by emergency nurses - Liti, Alessandro; Giusti, Gian Domenico; Gili, Alessio; Giontella, Mirella; Dell'Omo, Sara; Camerlingo, Vincenzo; Fronteddu, Alessandra; Galazzi, Alessandro; Bambi, Stefano (Acta Biomedica Atenei Parmensis, 2020)
Background: During medical emergencies, one of the main steps to improve patient outcomes is to achieve airway management. Orotracheal intubation is highly effective for advanced airway management, but it requires experienced health professionals. The use of a supraglottic airway device (SAD) is an acceptable alternative. Aim: To assess which of the four considered SADs takes the shortest time and the lowest number of attempts to be correctly placed. The secondary aim was to evaluate the influence of some characteristics of the study population on time taken and number of attempts required. Methods: A crossover trial was conducted at the Advanced Medical Simulation Center of the University of Perugia (Italy) between June and September 2017. Eighty-three nurses were enrolled in the study. Each participant was asked to place four different SADs in a manikin: Laryngeal Tube Suction-D (LTS-D), i-gel™, Ambu® Laryngeal Mask AuraGain™ and LMA® Protector™ Cuff Pilot™. Results: The median insertion time for the different devices was: 8.0 seconds (s) for LTS-D, 6.0 s for i-gel, 5.4 s for AuraGain, 5.8 s for LMA Protector (p